Hospital management information system / Yuhana Ashikin Ghazali - Yuhana Ashikin, Ghazali (2005)
This project is aimed to facilitate nurses with decision support feature and benefit the management of the hospital through increased speed or data manipulation, automated processing, essential report generation, and also good patient care services rendered using an efficient, reliable and new-friendly method of computerization to solve the shortcoming of drawbacks of the current systems used in hospitals in Malaysia today. This project, which focuses on research and development is developed using the latest most accepted technologies of today and hence would widely accepted by the hospital industry in Malaysia. The HMIS features automated workload assessment, defaulting charting respond, decision support, automated computations , charts form and reports data, and easier rostering process. The design of patient assessment application module and nursing care plan module captures nursing assessment and planning data using computer. The system also aimed to provide an efficient patient assessment recording, reduce costs, and improve discharge planning and early identification of patients needs. On the whole, the project is aimed to overcome the problems faced by the industry and expedite the processes involved in the health care sector. Object oriented methods development approach used to elicit functional requirements and to model proposed system.